Unveiling the Nexus: How Extension Delivery Methods Drive the Adoption of Improved Agronomic Practices among Cocoa Farmers in the Bono Region - Obeng Agyei, Rebecca; Amankwah, Kwadwo; Tham-Agyekum, Enoch Kwame; Narh, Esther; Quaye, Jonathan; Bakang, John-Eudes Andivi (Food, Agriculture and Natural Resources - NETWORKS, 2023)
The aim of this research is to investigate how different methods of delivering agricultural extension services influences the adoption of improved farming practices by cocoa farmers in the Bono Region. The study used data from 401 cocoa farmers selected through the multi-stage sampling technique. Generally, extension agents use farm visits and group meetings to facilitate the training of farmers on improved agronomic practices. Due to that, farmers perceived the use of farm visits and group meetings to be effective. We also found that farmers had a high level of knowledge on agronomic practices. The Tobit regression model was used to determine the effect of extension delivery methods on adoption of improved practices. The significant relationship found in this study between farm visits, group meetings, and the adoption of improved agronomic practices underscores the importance of targeted extension strategies that incorporate personalised interactions and group-based learning approaches to effectively promote agricultural innovation and sustainable farming practices. We recommend that the extension officers should frequently pay visits to the farmers and organise group meetings to improve the adoption of improved agronomic practices.